2018
DOI: 10.1016/j.autrev.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

The SLAM family receptors: Potential therapeutic targets for inflammatory and autoimmune diseases

Abstract: The signaling lymphocytic activation molecule (SLAM) family is comprised of nine distinct receptors (SLAMF1 through SLAMF9) that are expressed on hematopoietic cells. All of these receptors, with the exception of SLAMF4, are homotypic by nature as downstream signaling occurs when hematopoietic cells that express the same SLAM receptor interact. The SLAM family receptor function is largely controlled via SLAM associated protein (SAP) family adaptors. The SAP family adaptors consist of SAP, Ewing sarcoma associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 109 publications
(173 reference statements)
0
47
0
Order By: Relevance
“…The signaling lymphocytic activation molecule subfamily (SLAM; 9 members) is expressed on most immune cells ( Dragovich and Mor, 2018 ). SLAMs function as both co-stimulatory and co-inhibitory molecules in innate and adaptive immunity, and play an integral role in autoimmune disorders.…”
Section: Resultsmentioning
confidence: 99%
“…The signaling lymphocytic activation molecule subfamily (SLAM; 9 members) is expressed on most immune cells ( Dragovich and Mor, 2018 ). SLAMs function as both co-stimulatory and co-inhibitory molecules in innate and adaptive immunity, and play an integral role in autoimmune disorders.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, compared with the healthy control group, SLAMF1 was significantly down-regulated in patients with acute myocardial infarction (AMI) [ 28 ]. Evidence has been accumulating that SLAM family members are potential targets for inflammatory and autoimmune diseases [ 29 ]. Bacille Calmette-Guérin (BCG) infection significantly upregulated SLAMF1, which enhanced inflammatory response by activating the NF-κB signaling pathway [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD48 and 2B4 interact heterotypically with one another, whereas SLAM, Ly9, CD84, NTB‐A, CRACC, and BLAME are homophilic. References to putative homotypic interactions by SLAMF9 are found in the literature, but the origins of this assumption are unclear, because no published data exist showing self‐association by SLAMF9. In our studies on mouse SLAMF9, no evidence for self‐association was observed by SEC‐MALS (see Supplementary material, Fig. )…”
Section: Discussionmentioning
confidence: 99%